PEMBERDAYAAN MASYARAKAT DALAM SEKTOR PERTANIAN DI DESA KALIPITU KECAMATAN TOBELO TENGAH KABUPATEN HALMAHERA UTARA - MANDARASI, FESIANINDI; RURU, JOORIE MARHAEN; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2019)
The fundamental problem faced by the Farmers is the lack of interference from the Governmentin empowering the Kalipitu Village Community. Viewed from an economic perspective, the Local Potentialin the Village of Kalipitu constitutes the majority of Agriculture or crops, (nutmeg wija) such as tomatoes,vegetable onions, and corn. But the big question is, with so many plants in the Kalipitu Village it cannotempower the Community in the economic field, with this the Community is helpless and it turns out that theKalipitu Village Community only stands alone without any assistance, protection, and strength for theadvanced farmer Community to develop in technology agriculture, the lack of the Government's role in thewelfare of the Peasant Community in Kalipitu Village. this is seen from the lack of counseling, socialization,Â and assistance from the Government in developing the existing potential in the Kalipitu Village, there is noaction so that the community stops operating in farmer groups. The purpose of this study was to determinethe empowerment of KaliPitu Village Community in Central Tobelo District, North Halmahera Regency.This study uses a descriptive qualitative research method. Data collection techniques used are observation,interviews and data collection with documents. To see how the Community Empowerment of Kali PituVillage in the Agriculture sector in the District of Tobelo Tengah, North Halmahera Regency, VillageCommunities. Based on the results of research conducted on Kalipitu Village Community Empowerment inthe agricultural sector in Central Tobelo District, North Halmahera district, there has been no progress interms of increasing the economic income of the Village Community or in terms of empowering. This is dueto the lack of understanding and the lack of role of the Regional and Village Governments in payingattention to the Kalipitu Village Community. The suggestion is that there is a need for full attention fromthe Regional Government (Agriculture Office) and more specifically the Village Government in payingattention to the Kalipitu Village Community, in order to build coordination with the local Government.Keywords: Empowerment, Communities, Economic Development.